ATTENTION TO THE NEWBORN IN THE FAMILY HEALTH STRATEGY: ADVANCES AND CHALLENGES FOR INTEGRAL CARE - Maria Aparecida Munhoz Gaiva; Naudia Silva Dias; Valéria Carvalho Araújo Siqueira (Universidade Federal do Paraná, 2012)
This descriptive-exploratory study with a qualitative approach analyzed advances and challenges in care for the newborn resulting from the implantation of a family health center in Cuiabá in Mato Grosso. The data was collected through interviews and participant observation and was submitted to thematic content analysis. The subjects were a doctor, a nurse, two nurse technicians, four community health workers, and six mothers of newborns being monitored at the time of the data collection. Among the advances promoted by the Family Health Strategy is the improvement of access and of the link between service users and health professionals and of the solution of the care. The establishment of the team work and the participation of the family in the care are challenges to be overcome by the team in providing integral care to the newborn. It is concluded that from the perspective of integrality, in spite of the advances, greater valuing and incentivizing of the participation of the family in the care process is needed.